Design Of Fire Early Detection System Using Microcontroller As Smoke And Sprinkle Detection Using Fuzzy Mamdani Logic Method - Tengku Falih Diny Nurfikri; Sriani Sriani (Eduvest - Journal of Universal Studies, 2024)
This research presents the design of a fire early detection system utilizing a microcontroller integrated with Mamdani fuzzy logic. The system employs multiple sensors, including temperature, gas, and infrared sensors, to detect fires by analyzing the temperature, gas concentration, and fire distance. The microcontroller serves as the core processor that controls the sensors and triggers responses, such as alarms and sprinkler activation, based on fuzzy logic-based decision-making. Fuzzy logic enhances the system's adaptability to different fire severity levels, improving response accuracy. The system successfully detects potential fires, controls the sprinkler system automatically, and is shown to improve fire prevention in various environments. Testing results indicate that the system can effectively identify fire hazards and minimize damage by responding appropriately to various fire scenarios. This research provides a foundation for developing smarter and more efficient fire safety systems.